Studi Formulasi Kebijakan Perlindungan dan Pengembangan Pasar Tradisional di Daerah Istimewa Yogyakarta - Awan Santoso; Puthut Indroyono (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2011)
This study attempts to identify the various of the traditional market, which have suffered from marginalization caused by rapid expansion and penetration of modern supermarkets and other large retailers. As a way out, this recommends various protection strategies, which are based on provisions of the constitution and legislation and/or enacting new ones. Providing legal protection to sources of livelihood is common practice in many developed nations, where weak players are shielded from foreign player, and is also evident in other sectors and institutional aspects of the broader economy. The study recommends certain models of traditional markets development, which makes it a source of reference for various parties, market manager, government, local universities, and others.